Síntese e caracterização estrutural e magnética de compósitos do tipo xTiO2-(1-x)Fe3O4 - Silva, Michelle Queiroz da (2021)
Iron oxides and titanium oxides are of great scientific importance due to their magnetic, electrical, morphological, and physical-chemical properties, all of which enable various applications such as catalytic processes, semiconductors, spintronics etc. Among the mixed binary oxides, systems of the type Fe2-yTiO3, a series of solid solutions with compositions between hematite (α-Fe2O3) and Ilmenite (FeTiO3), have attracted the interest of theoretical and experimental areas due to their magnetic characteristics (antiferromagnetic with weak ferromagnetism). In this work, we synthesized compounds of the type xTiO2-(1-x) Fe3O4 by means of high-energy ball milling, with x = 0.2; 0.4; 0.6; 0.8, of which we selected the concentration x = 0.2 for a more detailed analysis. For the synthesis of the composites, we used the precursor powders TiO2 (anatase) and Fe3O4 (synthesized here by means of coprecipitation), and both were stoichiometrically mixed and milled in a ball mill for 24 hours. Subsequently, we submitted the resulting samples to heat treatment at temperatures of 700°C, 900°C and 1100°C for 3 h. After that, the composites were characterized through X-ray diffraction, vibrant sample magnetometry, and Mössbauer spectroscopy. In magnetic characterization were used the Physical Properties Measurements System – PPMS to obtain ZFC/FC curves, magnetic susceptibility, and magnetization by different treatment temperatures. The X-ray diffraction profiles of the milled samples did not indicate the formation of new crystalline phases. For the milled sample submitted to heat treatment, the presence of ilmenite (FeTiO3) and hematite (α-Fe2O3) was observed, with the former presenting phase concentration of 100% at the temperature of 1100°C. Magnetic analysis and Mössbauer spectroscopy revealed the presence of Fe2+ and Fe3+ ions. The combined system FeTiO3-α-e2O3 was characterized as titanohematite. The sample calcined at a temperature of 700°C also showed behavior compatible with the dynamics of spin glass. The results found suggest to the obtainment of high-quality FeTiO3-αFe2O3 and FeTiO3 composites from synthesis and accessible thermal treatments with several applications in the field of condensed matter physics.